Recycled versus Natural-Rubber Fiber-Reinforced Bearings for Base Isolation: Review of the Experimental Findings. Issue 4 (12th March 2022) - Losanno, D.; Calabrese, A.; Madera-Sierra, I. E.; Spizzuoco, M.; Marulanda, J.; Thomson, P.; Serino, G.
ABSTRACT: Over the last decade, significant efforts have been dedicated to develop novel low-cost seismic protection systems that could be used on a large scale in developing regions of the world. In the attempt of reducing the cost of conventional base isolation devices, the feasibility of using flexible reinforcements to replace the steel sheets of traditional steel-reinforced elastomeric isolators (SREIs) has been validated. It has also been verified that these bearings can be installed in unbonded configurations. Previous research has verified the performance of fiber-reinforced elastomeric isolators in unbounded configuration (U-FREIs) using recycled elastomers. The use of recycled rubber to manufacture U-FREIs is very appealing because of its low-cost and its limited environmental impact. In this paper a thorough comparison of the performance of natural-rubber unbounded fiber-reinforced elastomeric isolators (NU-FREIs) and that of recycled rubber bearings (RU-FREIs) is proposed. To this end, the paper discusses the manufacturing and the main features of the two different technologies, as well as the results of experimental tests on the devices and small-scale structures tested on a shaking-table. Overall, the performance of NU-FREIs was found to be better than that of RU-FREIs. Nevertheless, recycled rubber devices are very promising when it comes to protecting non-engineered constructions from moderate to high seismic inputs at a fraction of the cost of conventional technologies.